If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -9)(9x + 9) = 0 Reorder the terms: (-9 + 7x)(9x + 9) = 0 Reorder the terms: (-9 + 7x)(9 + 9x) = 0 Multiply (-9 + 7x) * (9 + 9x) (-9(9 + 9x) + 7x * (9 + 9x)) = 0 ((9 * -9 + 9x * -9) + 7x * (9 + 9x)) = 0 ((-81 + -81x) + 7x * (9 + 9x)) = 0 (-81 + -81x + (9 * 7x + 9x * 7x)) = 0 (-81 + -81x + (63x + 63x2)) = 0 Combine like terms: -81x + 63x = -18x (-81 + -18x + 63x2) = 0 Solving -81 + -18x + 63x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9'. 9(-9 + -2x + 7x2) = 0 Factor a trinomial. 9((-1 + -1x)(9 + -7x)) = 0 Ignore the factor 9.Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(9 + -7x)' equal to zero and attempt to solve: Simplifying 9 + -7x = 0 Solving 9 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -7x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -7x = 0 + -9 -7x = 0 + -9 Combine like terms: 0 + -9 = -9 -7x = -9 Divide each side by '-7'. x = 1.285714286 Simplifying x = 1.285714286Solution
x = {-1, 1.285714286}
| (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 | | 4p-17.0=53.00 | | 0.1x=0.35 | | 9x-2y/3*5z | | 0.35x=0.1 | | -8y-10xy= | | 0.1x-0.01x=1 | | -5b-b= | | -2x^2+3x^2= | | -2x^2-3x^2= | | 3x/5-0.5=109 | | 2x-3/3-(x-5)=x/3 | | -5(2x+10)=6(-3x+20) | | 100-53.25= | | g(v)=cosv/cscv | | CosV/CscV | | 2(x+5)=-3(x+10) | | w^2+6w+11=0 | | Tan31=x/3 | | x^2+2ax+(a+6)=0 | | X^3-6x^2=63504 | | 85=7+5x | | 2m^2+3m-17=0 | | u(x)=e(-0.1x) | | 6a+b=0 |